Massification of youth religious studies to prevent juvenile delinquency in Bandung - Rahman, Mohammad T. (HTS teologiese studies, 2021)
This article suggests that social media and public spaces in contemporary Indonesia play an essential role as a context for Islamic ideologisation by developing social mobilisation methods and transforming its ideology and culture. This socio-phenomenological study highlights the historical and social processes that underlie pious youth’s rise in an Indonesia’s contemporary urban space, for example, Bandung. The Hijrah [Migrating] Youth Community is an Islamic movement based on mosques and social media such as Twitter, Facebook and YouTube to migrate Hijrah to a better life. This study draws on the forms of articulation culture that emerged from the ideals of the revival and reinvention of Islam in the materiality of secular popular culture. The religious activities of Hijrah youth may reduce the disorders of young people, however since the young are rebellious, extreme religious activities may also arise from the community. Thus, different parties, especially parents, the Bandung City government and other social institutions must supervise the development of the youths’ life based on religious parties.Contribution: This study describes the operation of a youth religious movement, which tries to overcome the problem they usually face, namely juvenile delinquency. This study can develop research patterns that can analyse social phenomena and and apply them to policy consideration.